Application of Pisang Awak Bunch-Derived Heterogenous Base Catalyst in Transesterification of Palm Oil into Biodiesel - Meriatna Meriatna; Zulmiardi Zulmiardi; Suryati Suryati; Sulhatun Sulhatun; Zukhrufi Dina Nasution; Rahmadhani Rahmadhani (Malikussaleh University, Aceh, Indonesia, 2022)
Biodiesel is an alternative fuel for diesel machine comprosied of alkyl monoesters deriving from vegetable oils or animal fats. Cooking oil is an oil originated from vegetable or animal fat which has been priorly purified, where it appears in liquid form at room temperature and is usually used to fry food ingredients. Heterogenous catalyst is a catalyst present in different phase with the reagent in a reaction it catalyzes. Kalium content in banana in a banana bunch is sufficiently high reaching 94.4%. The aim of this study was to utilize banana bunch which has been priorly ashed using furnace at 700Â°C for 4 hours, thereafter, applied as a heterogenous catalyst in a the preparation process of biodiesel from cooking oil. Processing variables investigated in this research included the influences of the number of catalyst (3, 4, 5, 6, and 7%) and molar rasio of oil and methanol (1:5, 1:6, 1:7, 1:8, and 1:9) against the properties of produced biodiesel, namely density, viscosity, and water content which later compred with Indonesian standard (SNI). From the study, it was obtained maximum yield of 90.97% with methanol:oil rasio of 1:7 at processing temperature of 60Â°C with reaction time of 90 minutes and catalyst as much as 3 % w/w. The characteristics of the cooking oil-based biodiesel obtained from the a reaction with oil: methanol rasio of 1:6 and catalyst as much as 3% w/w were density 850 kg/m3 and viscosity 621 mm2/s. This research showed that the obtained biodiesel characteristics had been sufficient according to the SNI, and the use of calcinated banana bunch was very potential in the production of biodiesel acting as solid catalyst person.